50 Diagnostic role of exercise tolerance testing in familial premature sudden cardiac death. (9th June 2011) - Raju, H; Papadakis, M; Bastiaenen, R; Zaidi, A; Chandra, N; Muggenthaler, M; Spath, N; Sharma, S; Behr, E R
Abstract : Background: Investigation of blood relatives for evidence of an inherited cardiac condition is advocated following an unexplained sudden cardiac death (SCD). Aim: We determined the diagnostic yield of exercise tolerance testing (ETT) in investigation of inherited cardiac conditions following familial premature SCD. Methods: Between 2006 and 2010, we evaluated 308 blood relatives of 148 SCD victims, who completed at least 3 min of the Bruce protocol. ETTs were analysed for: QT prolongation; Brugada type 1 pattern; ST depression: blood pressure (BP) response; multiple ventricular ectopics or arrhythmia. Individual pathological phenotypes were determined by a combination of 12-lead ECG, echocardiogram, 24-h holter monitor, with additional MRI, CT coronary angiography and genetic mutation analysis, as appropriate. Results: Thirty (9.8%) patients had an abnormality during ETT, details of which are summarised in Abstract 50 figure 1 . All ETTs with abnormal QT prolongation and dynamic Brugada pattern were associated with diagnoses of long QT syndrome and Brugada syndrome respectively. An example of dynamic Brugada phenotype is given in Abstract 50 figure 2 . Ventricular ectopy was seen in 15 patients, of whom 5 demonstrated phenotypic cardiomyopathy or channelopathy on further investigations. No patients with significant ST depression had evidence of coronary abnormalities on imaging. No hypotensive BP response was seen, but exertional hypertension was associated with systemic hypertension. Conclusion: The ETT is a useful diagnostic adjunct when evaluating relatives of victims of premature SCD. Reliable diagnostic indicators include inappropriate QT prolongation and dynamic Brugada pattern. Ventricular ectopy is non-specific, but is associated with both cardiomyopathic and channelopathic processes in a significant minority. ST segment depression, however, is unhelpful and should be viewed in the context of the patient's cardiovascular risk profile.